The ISOPAR method: A new approach to performance analysis in golf - Stöckl, M.; Lamb, P. F.; Lames, M. (Journal of Quantitative Analysis in Sports, 2011)
Classical performance analysis techniques in golf have focused on classes of shots, such as putting, driving, etc. Because these measures remove shots from their original context within the round, such measures do not describe a player's ability to perform a specific type of shot. Rather, these measures provide a score which is a composite score of all previous shots on the hole. This study establishes a new method for assessing the difficulty of shots in golf and a new performance indicator — Shot Quality. We call our method the "ISOPAR method," which gets its name from the analogy we make to isobar maps used in meteorology. The method presented here relies on ball positions taken from tournament play and the associated number of shots required to hole out from each measured ball position. Data were collected from the 2009 Bavarian Junior Championship in Burgwalden, Germany. ISOPAR values are calculated which represent the average number of strokes required to hole out from any location on the green. These ISOPAR values can be visualized on an ISOPAR map. Instead of lines of equal pressure, as in the case of our meteorological analogy, the lines on the map represent the ISOPAR values at intervals of 0.2. High values can be interpreted as difficult areas on the green and low values as easy areas on the green. The Shot Quality score is the difference between the ISOPAR values of the starting position and finishing position, respectively. ISOPAR maps could potentially be used by professional golfers and caddies to characterize a green in terms of areas of difficulty and may also help them decide which putts to play more or less aggressively. Television broadcasts could also use these maps to show the audience how the field fared from various positions on the green. Finally, coaches and teachers could use the Shot Quality measure as a new performance indicator to assess shot outcomes.